Effects of Yogurt with Carao (Cassia grandis) on Intestinal Barrier Dysfunction, α-glycosidase Activity, Lipase Activity, Hypoglycemic Effect, and Antioxidant Activity - Ricardo S. Aleman; Jhunior Marcia; Ryan Page; Shirin Kazemzadeh Pournaki; Daniel Martín-Vertedor; Víctor Manrique-Fernández; Ismael Montero-Fernández; Kayanush Aryana (Fermentation, 2023)
Cell inflammation disrupts intestinal barrier functions and may cause disorders related to a leaky gut, possibly leading to diabetes. The objective of this study was to determine if carao (Cassia grandis) incorporated into yogurt enhances in vitro intestinal barrier function. To achieve this goal, Caco-2 cells were used as a model of intestinal barrier permeability. Caco-2 cells were treated with cytokines (interleukin-1β, tumor necrosis factor-α, interferon-γ, and lipopolysaccharide (LPS)) and yogurt with carao yogurt (CY) at different doses (1.3 g/L, 2.65 g/L, and 5.3 g/L). Real-time quantitative polymerase chain and immunofluorescence microscopy were applied to evaluate the expression and localization of tight junction proteins. Functional effects of the formulation of yogurt supplemented with carao were also evaluated in terms of the antioxidant activity, the α-glycosidase activity, and lipase inhibitory properties. In addition, the hypoglycemic potential was validated in vivo in a rat model. Compared to the control yogurt, Caco-2 TEER (transepithelial electrical resistance evaluation) by yogurt with 5.3 g/L of carao was significantly lower (p < 0.05) after 48 h. Yogurt with 5.3 g/L of carao had a considerably lower permeability (p < 0.05) than control yogurt in FD and LY flux. Yogurt with 5.3 g/L of carao enhanced the localization of ZO-1. Carao addition into yogurt increased the flavonoid content, apparent viscosity, lipase inhibition activity, and α-glycosidase activity. The rats fed with the yogurt with 5.3 g/L of carao demonstrated a higher blood glucose modulation.